1995
DOI: 10.1021/bi00001a044
|View full text |Cite
|
Sign up to set email alerts
|

Water Requirements in Monomer Folding and Dimerization of Triosephosphate Isomerase in Reverse Micelles. Intrinsic Fluorescence of Conformers Related to Reactivation

Abstract: The possibility of using reverse micelles to stabilize monomers prior to formation of dimeric triosephosphate isomerase (TPI) from rabbit muscle was studied. TPI denatured with guanidine hydrochloride undergoes reactivation in reverse micelles formed with n-octane, hexanol, cetyltrimethylammonium bromide, and water. Reactivation of around 80% is observed at TPI concentrations of about 2 micrograms/mL of reverse micelles and water concentrations above 4.0%. With 3.0% water, reactivation is about 10%. If denatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
11
0
1
Order By: Relevance
“…18 Another study of rabbit TIM folding found no evidence for an intermediate when the protein was folded in water, but did find evidence for an intermediate when the protein was folded in reverse micelles. 19 Neither the structure nor the affects of the micellar environment on the folding process were determined. Results of another study on rabbit muscle TIM folding in reverse micelles, but using FRET measurements, suggested that the intermediate may be an inactive dimer.…”
Section: Partially Folded Intermediates In Tim Folding/ Unfoldingmentioning
confidence: 99%
“…18 Another study of rabbit TIM folding found no evidence for an intermediate when the protein was folded in water, but did find evidence for an intermediate when the protein was folded in reverse micelles. 19 Neither the structure nor the affects of the micellar environment on the folding process were determined. Results of another study on rabbit muscle TIM folding in reverse micelles, but using FRET measurements, suggested that the intermediate may be an inactive dimer.…”
Section: Partially Folded Intermediates In Tim Folding/ Unfoldingmentioning
confidence: 99%
“…Water requirements in monomer folding and dimerization of triosephosphate isomerase in reverse micelles have been uncovered by Fernandez-Velasco et al [3], and these studies have led to the concept that water is fundamental in the function and stability of a protein [3,26,27]. However, the precise contribution of water and particularly how much water is needed for protein folding are not well understood so far.…”
Section: Discussionmentioning
confidence: 99%
“…So far several groups have already investigated protein refolding and unfolding in reverse micelles [3][4][5][6][7]. FernandezVelasco and colleagues have found that water plays important roles in monomer folding and dimerization of triosephosphate isomerase in reverse micelles [3]. Shastry and Eftink have observed a reversible transition of thermal unfolding of RNase T1 in reverse micelles [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite being one of the ®rst glycolytic enzymes to be puri-®ed (Krietsch et al, 1970;Scopes, 1977), the structure of rabbit muscle TIM has not yet been reported. The amino-acid sequence of this protein is known (Corran & Ley, 1975) and its kinetic properties have been extensively studied (Garza-Ramos et al, 1992;Fernandez-Velasco et al, 1995) and compared with those of T. brucei brucei and yeast (Saccharomyces cerevisiae) TIMs (Lambeir et al, 1987). Biophysical studies of the enzyme have been carried out by infrared spectroscopy (Castresana et al, 1988) and electron microscopy (Tanaka et al, 1994).…”
Section: Introductionmentioning
confidence: 99%